The dance as means of body knowledgefor adolescent health promotion - Costa, Anny G.M.; Monteiro, Estela M.L.M.; Vieira, Neiva F.C.; Barroso, Maria G.T. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: the integration of art and dance to the nursing action in a context of health education is an innovation idea that can involve adolescents as asubject in the behavior change, in which improves nurse’s performance for health promotion. The dance constitutes a resource of corporal awareness whenassociating the motivation for expression, movement, balance, body knowledge and relationship to the social environment. Objective:to apply thePractical Educative Dance Program (PEDP) as health education strategy for adolescents and to describe their improved knowledge on health, sexuality andSTD/AIDS by means PEDP. Method:descriptive study based on qualitative approach. The study was in a public school in Fortaleza. A number of 28 ado-lescents at the age between 12 and 15 years old participated in the study. They attended basic education. The adolescents attended 12 meetings weekly.Each meeting lasted 90 minutes and discussed concepts of body, movement and behavior. Result:Data was organized in six mains themes and conceptualcategories: 1. Sensitization body, balance and position; 2. Life experience, body expression and interpersonal relations, decision-making, solidarity; 3.Selfesteem and Confidence, coping; 4. Place and Time – Life, place and work; 5. Body comprehension and Sexuality – knowledge, body, prevention,SDT/AIDS; 6.Learning and dissemination – performance, peers education evaluation. Conclusion:the PEDP contributed for adolescents’ participationand helped to discuss sensitive issues and smoothly talks among participants. Thus adolescents improved their knowledge about health, STD/aids, bodyand values such solidarity, confidence. The results demonstrated that the method may apply in other adolescent groups.